The gene
Clearly and simply presents basic information on one of the most important concepts in modern science-the gene. New computer animations help clarify the concepts. Part 1 : how genes were discovered. Dramatizes the history of genetic discovery from Mendel in his monastery garden to Watson and Crick at the Cavendish Laboratory in England. Part 2 : what is a gene and how does it work? Outlines the basic picture we have today of what a gene is and how it works. Includes new material on cloning and the human genome project. In the gene the keys to scientific literacy include: adenine, amino acids, biochemist, chromosomes, cloning, Francis Crick, cytosine, differentiation, DNA, double helix, enzymes, Rosalind Franklin, gene gun, genetics, genome project, guanine, meiosis, Gregor Mendel, mitosis, mutation, ovary, protein, restriction enzyme, RNA, thymine, James Watson.